2017
DOI: 10.1080/14767058.2017.1369520
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics for the management of neonatal hyperbilirubinemia: a systematic review of randomized controlled trials

Abstract: Limited low-quality evidence indicates that probiotic supplementation may reduce the duration of phototherapy in neonates with jaundice. Routine use of probiotics to prevent or treat neonatal jaundice cannot be recommended. Large well-designed trials are essential to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 26 publications
2
25
0
3
Order By: Relevance
“…9,10 Newborns with ABO or Rh incompatibility were excluded from these studies. Deshmukh et al 11 reported that probiotic supplementation may reduce the duration of phototherapy in neonates with jaundice. These inconsistent results may be related to the doses of probiotic bacteria strains or types employed, and their ability to survive and proliferate in the intestinal environment.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Newborns with ABO or Rh incompatibility were excluded from these studies. Deshmukh et al 11 reported that probiotic supplementation may reduce the duration of phototherapy in neonates with jaundice. These inconsistent results may be related to the doses of probiotic bacteria strains or types employed, and their ability to survive and proliferate in the intestinal environment.…”
Section: Discussionmentioning
confidence: 99%
“…Neonatal jaundice is present in >50% of full-term newborns and it is more serious in late-preterm infants (1,2). Neonatal jaundice may be classed as physiological or pathological (3,4) and is principally caused by an increase in serum bilirubin during the neonatal period, which causes yellow discoloration of the skin, mucous membranes and sclerae (5). Neonatal hyperbilirubinemia is caused by an increase in blood bilirubin levels above the normal range.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, studies [24] have shown that probiotic supplementation can shorten the phototherapy time of neonatal jaundice. Preventive probiotics can not signi cantly reduce the incidence of jaundice.…”
Section: Discussionmentioning
confidence: 99%